The Intimate Relationship between Vestibular Migraine and Meniere Disease: A Review of Pathogenesis and Presentation - Yuan F. Liu; Helen Xu (Behavioural Neurology)
Vestibular migraine (VM) has only recently been recognized as a distinct disease entity. One reason is that its symptoms overlap greatly with those of other vestibular disorders, especially Meniere disease (MD). The pathophysiology of neither VM nor MD is entirely elucidated. However, there are many theories linking migraine to both disorders. We reviewed the current understanding of migraine, VM, and MD and described how VM and MD are similar or different from each other in terms of pathophysiology and presentation, including hypotheses that the two share a common etiology and/or are variants of the same disease.